Sense of alexithymia in patients with anxiety disorders comorbid with recurrent urticaria - Oglodek E; Szota AM; Just M; Araszkiewicz A; Szromek AR (Neuropsychiatric Disease and Treatment)
Ewa A Ogłodek,1 Anna M Szota,1 Marek J Just,2 Aleksander Araszkiewicz,1 Adam R Szromek3 1Department of Psychiatry, Collegium Medicum in Bydgoszcz, Nicolaus Copernicus University in Torun, Toruń, 2Department of General and Endocrine Surgery, Municipal Hospital, Piekary Śląskie, 3Department of Organization and Management, Silesian University of Technology, Gliwice, Poland Aim: Alexithymia is associated with limited cognitive processing of emotions by an individual suffering from recurrent urticaria and alexithymia and makes them focus on somatic manifestations of emotional arousal and on poorly controlled compulsive reactions to negative stimulation. Alexithymia is considered to be a personality trait, which, along with other factors, predisposes individuals toward developing somatic diseases. The aim of the study was to assess the measurement of alexithymic features in patients with recurrent urticaria and to assess the types of concurrent anxiety disorders and overall anxiety level.Methods: In order to diagnose clinical anxiety symptoms in patients, the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition and the Hamilton Anxiety Rating Scale were applied. Alexithymic features were measured by means of a shortened version of the Toronto Alexithymia Scale, characterized by high discrimination power, internal coherence, and reliability.Results: According to the Toronto Alexithymia Scale results, the greatest contributing factor was “inability to differentiate between feelings and bodily sensations”. This was observed in both males and females. Most frequently, the patients were found to suffer from generalized anxiety disorder and social phobia.Conclusion: Alexithymia may result from the difficulty associated with expressing emotions caused by anxiety disorders. Undergoing treatment for anxiety disorders may contribute to reduced exacerbation of urticaria. Keywords: alexithymia, anxiety, recurrent urticaria